The Influence Of Service Quality And Price Discounton Purchasing Decisions In Panenka Sports Sttore In Bengkulu - Hafi Ihza Mahendra; Ade Tiara Yulinda (PT. MEMIKATTA PUBLISHER INDONESIA, 2024)
The aim of the research is to determine the effect of service quality and price discounts on purchasing decisions at Panenka sports store in Bengkulu. And to find out which factors most dominantly influence purchasing decisions.his research used quantitative methods on 75 respondents. The population used in this research is consumers of the Panenka Sport Sports Shop and sampling in this research is a non-probability sampling technique.Based on the results of multiple linear regression, the regression equation Y = 1.312 + 0.690 (X_1) + 0.158 (X2) is obtained. The results of the research concluded that service quality and price discounts had a positive and significant effect, partially or simultaneously, on purchasing decisions at the Panenka Sport Sports Store in Bengkulu.